CURRENCY AND OUTCOMES IN ARTERIAL HYPERTENSION PATIENTS WITH DIFFERENT TYPES OF SYSTOLIC ARTERIAL BLOOD PRESSURE ORTHOSTATIC REACTIONS - Iegorova, A. Yu.; Garkaviy, P. O.; Yablucnasky, M. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Peculiarities of currency and outcomes in arterial hypertension (AH) patients with hypotensive, isotensive and hypertensive orthostatic reactions (OR) of systolic arterial blood pressure (SBP) were studied in the follow up of 113 AH patients, age 64,73±6,42 years. 44 males and 69 females. According to the SBP in orthostatic test patients were divided into 3 groups: group 1 – hypotensive OR, group 2 – isotensive OR and group 3 – hypertensive OR. AH grades and stages frequencies, HF functional class after 4 years of treatment, and the severity and frequency of adverse cardiovascular events and outcomes were identified. Data was processed by the variation statistics methods. It was found that the less severe currency of AH is seen in hypertensive type, more severe in hypotensive type, and the most severe in isotensive type of SBP orthostatic reactions. In general quantity of adverse events and outcomes is more frequently seen in isotensive type of SBP OR – 46%, is less frequently seen in hypertensive type – 18%. In AH patients it is necessary to pay special attention not only to the BP control, but also to the optimization of SBP orthostatic reactions.